Mental health and disability research priorities and capacity needs in Ghana: findings from a rapid review and research priority ranking survey - Benedict Weobong; Kenneth Ae-Ngibise; Grace Mwangi; Lionel Sakyi; Crick Lund (Taylor & Francis Group, 2022)
Background Identification of national research agendas for mental health and disability can be supported by well-designed research priority-setting studies. Few low- and middle-income countries (LMICs) have undertaken such studies. Objective To identify mental health and disability research priorities in Ghana. Methods A mixed methods study comprising a rapid review, research priority ranking survey, and research capacity needs assessment survey was employed. Participants in the surveys included five expert pools identified from online search and existing database on mental health civil society organisations/non-governmental organisations. The research priority ranking was completed in two stages, using the Child and Nutrition Research Initiative (CHNRI) method to identify priority questions for immediate and short term (0 to 5 years) and medium to long term (>5 years) in stage two. Both surveys were deployed online using google forms. Analysis for the ranking survey involved computing total scores from the CHNRI criteria and generating ranks for the research questions. Results A total of 68 experts (97% response rate), generated 94 and 92 questions for the short and long term, respectively. Forty experts (58% response rate) completed the ranking stage. The top 10 ranked research questions included: 4 questions addressing health systems; 2 questions on epidemiology; and 4 questions on interventions. All research questions were considered urgent and should be conducted in the immediate to short term (0-5 years). The methodological capacity of researchers to conduct disability and mental health research is weak. Conclusion Our approach has generated an agenda for mental health and disability research priorities for Ghana and demonstrated that it is feasible to employ a systematic methodology for research priority setting that includes key parameters of context and research capacity.